Approximation models of fractional order dynamic systems using interpolation-extrapolatory method - Сімак, Л.О.; Тодорова, Г.М. (Proceedings of National Aviation University (archive), 2012)
Spectral approach to the modeling of the fractional dynamic systems is considered. Interpolation-extrapolatory method is used for approximation.